The Effect of Employee Development on Employee Performance Through Work Motivation at the Forestry Service of East Kalimantan Province - Caldas, Rodrigo Santos Caldas Goncalves; Istimaroh,; Fitriansyah, (Research in Management of Technology and Business, 2024)
This study aims to determine the influence of employee development on employee performance through motivation in the East Kalimantan Provincial Forestry Service. This research is based on the existence of competition between other government agencies in national development supported by data quoted from sindonews stating that lack of coordination and collaboration can hinder employee performance. This study uses quantitative data. The data source in this study uses primary data by distributing a questionnaire in the form of a Google Form to employees of the East Kalimantan Provincial Forestry Service. The population in this study is all employees in the East Kalimantan Provincial Forestry Service and received a sample of 156 respondents who were taken by probability sampling method using simple random sampling. data analysis techniques in this study using IBM SPSS Version 26 and SmartPLS software version 4.0.2. The results in this study indicate that employee development has a positive and significant effect on employee performance, career development has a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance, and employee development has a positive and significant effect on employee performance through work motivation. Suggestions that can be given in this study pay more attention to training, education and are supported by providing maximum motivation in order to develop the career of each employee and also improve employee performance. The benefits of this research are knowledge and insight for researchers in the field of human resource management, especially regarding employee development, work motivation and employee performance.